Exploring the plant environmental DNA diversity in soil from two sites on Deception Island (Antarctica, South Shetland Islands) using metabarcoding. Issue 5 (October 2021) - Carvalho-Silva, Micheline; Rosa, Luiz Henrique; Pinto, Otávio H.B.; Da Silva, Thamar Holanda; Henriques, Diego Knop; Convey, Peter; Câmara, Paulo E.A.S.
Abstract: The few Antarctic studies to date to have applied metabarcoding in Antarctica have primarily focused on microorganisms. In this study, for the first time, we apply high-throughput sequencing of environmental DNA to investigate the diversity of Embryophyta (Viridiplantae) DNA present in soil samples from two contrasting locations on Deception Island. The first was a relatively undisturbed site within an Antarctic Specially Protected Area at Crater Lake, and the second was a heavily human-impacted site in Whalers Bay. In samples obtained at Crater Lake, 84% of DNA reads represented fungi, 14% represented Chlorophyta and 2% represented Streptophyta, while at Whalers Bay, 79% of reads represented fungi, 20% represented Chlorophyta and < 1% represented Streptophyta, with ~1% of reads being unassigned. Among the Embryophyta we found 16 plant operational taxonomic units from three Divisions, including one Marchantiophyta, eight Bryophyta and seven Magnoliophyta. Sequences of six taxa were detected at both sampling sites, eight only at Whalers Bay and two only at Crater Lake. All of the Magnoliophyta sequences (flowering plants) represent species that are exotic to Antarctica, with most being plausibly linked to human food sources originating from local national research operator and tourism facilities.